Six Principles for Embracing Gender and Sexual Diversity in Postsecondary Biology Classrooms. (16th March 2022) - Zemenick, Ash T; Turney, Shaun; Webster, Alex J; Jones, Sarah C; Weber, Marjorie G
Abstract: Sexual and gender minorities face considerable inequities in society, including in science. In biology, course content provides opportunities to challenge harmful preconceptions about what is "natural" while avoiding the notion that anything found in nature is inherently good (the appeal-to-nature fallacy). We provide six principles for instructors to teach sex- and gender-related topics in postsecondary biology in a more inclusive and accurate manner: highlighting biological diversity early, presenting the social and historical context of science, using inclusive language, teaching the iterative process of science, presenting students with a diversity of role models, and developing a classroom culture of respect and inclusion. To illustrate these six principles, we review the many definitions of sex and demonstrate applying the principles to three example topics: sexual reproduction, sex determination or differentiation, and sexual selection. These principles provide a tangible starting place to create more scientifically accurate, engaging, and inclusive classrooms.